2021
DOI: 10.1016/j.diabres.2020.108636
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of TCF7L2 gene and its coherence with metabolic parameters in Lithuanian (Kaunas district) women population with previously diagnosed gestational diabetes mellitus compared to general population

Abstract: To determine the association of genetic variants rs7901695, rs7903146, rs7895340, rs11196205, rs12255372 of transcription factor 7 like 2 (TCF7L2) gene and its coherence with metabolic parameters in Lithuanian (Kaunas district) women population with previously diagnosed gestational diabetes mellitus (GDM) and to compare the prevalence of TCF7L2 single nucleotide polymorphism (SNP) results to general population. Methods: Women with previously diagnosed GDM participated in the study. Anthropometric measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This study found that the minor allele frequency (MAF) of rs7903146 was 41%, whereas other studies have shown inconsistent results across countries and regions. For example, the frequency of this allele is 10.5% in Malaysia [ 45 ], 3.3% in South Korea [ 46 ], 2% in China [ 29 ], 36.4% in Qatar [ 47 ], 33% in Poland [ 25 ], 36.2% in Spain [ 48 ], 74% in Lithuania [ 49 ], 38.8% in India, 24% in Bangladesh [ 50 ], 23% in Mexico [ 27 ], 48.4% in Australia [ 51 ], and 27.6% in Denmark [ 52 ]. The MAF of the rs2237892 SNP in this population was determined to be 9%, with a prevalence of 8.3% in Poland [ 35 ], which is quite close to our study.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the minor allele frequency (MAF) of rs7903146 was 41%, whereas other studies have shown inconsistent results across countries and regions. For example, the frequency of this allele is 10.5% in Malaysia [ 45 ], 3.3% in South Korea [ 46 ], 2% in China [ 29 ], 36.4% in Qatar [ 47 ], 33% in Poland [ 25 ], 36.2% in Spain [ 48 ], 74% in Lithuania [ 49 ], 38.8% in India, 24% in Bangladesh [ 50 ], 23% in Mexico [ 27 ], 48.4% in Australia [ 51 ], and 27.6% in Denmark [ 52 ]. The MAF of the rs2237892 SNP in this population was determined to be 9%, with a prevalence of 8.3% in Poland [ 35 ], which is quite close to our study.…”
Section: Discussionmentioning
confidence: 99%